Nebulized amphotericin B for preventing exacerbations in allergic bronchopulmonary aspergillosis: A systematic review and meta-analysis - Muthu, Valliappan; Dhooria, Sahajal; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Rudramurthy, Shivaprakash M.; Aggarwal, Ashutosh N.; Chakrabarti, Arunaloke; Agarwal, Ritesh (Pulmonary pharmacology & therapeutics, 2023)
Allergic bronchopulmonary aspergillosis (ABPA) is complicated by exacerbations in more than one-third of the subjects. Whether nebulized amphotericin B (NAB) therapy prevents ABPA exacerbations remains unclear. The primary objective of this systematic review and meta-analysis was to determine the frequency of subjects remaining exacerbation-free, one year after initiating NAB. The key secondary objectives were the time to first exacerbation and the safety of NAB therapy. We searched the PubMed and Embase databases for studies evaluating ≥5 subjects of ABPA managed with NAB. We report the pooled proportion of ABPA subjects remaining exacerbation free after one year. For the randomized controlled trials (RCTs), we estimate the pooled risk difference (RD) of exacerbation-free status at one year with NAB versus the control arm. We included five studies for our analysis; three were observational (n = 28) and two RCTs (n = 160). The pooled proportion (95% confidence interval [CI]) of subjects remaining exacerbation free with NAB at one year was 76% (62–88). The pooled RD (95% CI) of an exacerbation-free status at one year was 0.33 (−0.12 to 0.78) and was not significantly different between the NAB and control arms. The time to first exacerbation was longer with NAB than with the standard therapy. No serious adverse events were reported with NAB. NAB does not improve exacerbation-free status at one year; however, weak evidence suggests it delays ABPA exacerbations. More research using different dosing regimens is required.